1997
DOI: 10.1007/s003590050036
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila antenna: ultrastructural and physiological studies in wild-type and lozenge mutants

Abstract: The physiology and ultrastructure of the antenna in Drosophila melanogaster have been examined in wild-type and lozenge mutants. Scanning electron microscopy (SEM) of sensilla on the antennal surface has revealed that in the wild-type the basiconic sensilla contain linear arrays of pores connected by longitudinal furrows and transected by shorter furrows. Sensilla trichodea also are shown to have pores, as revealed by examining transverse sections by transmission electron microscopy (TEM); these data directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…These data showed that s. basiconica fell into different functional types, with different types responding to different subsets of odors, and distributed in different subregions of the antennal surface. There are few if any data from s. trichodea and s. coeloconica of Drosophila, and in fact until recently there has been controversy as to whether s. trichodea were likely to have olfactory function (Venkatesh and Singh, 1984;Stocker, 1994;Riesgo-Escovar, et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…These data showed that s. basiconica fell into different functional types, with different types responding to different subsets of odors, and distributed in different subregions of the antennal surface. There are few if any data from s. trichodea and s. coeloconica of Drosophila, and in fact until recently there has been controversy as to whether s. trichodea were likely to have olfactory function (Venkatesh and Singh, 1984;Stocker, 1994;Riesgo-Escovar, et al, 1997).…”
Section: Introductionmentioning
confidence: 97%
“…The -220 s. basiconica fall into two morphological subtypes: large s. basiconica are 2-3.5 ~um in diameter (Venkatesh and Singh, 1984) and approximately 10 ~um in height (Riesgo-Escovar et al, 1997); small s. basiconica are approximately 1.7 ~um in diameter and 8 jam in height (Riesgo-Escovar et al, 1997). Both classes of s. basiconica contain pores through which odors are believed to pass, and they contain either 2 or 4 neurons.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The surface of the funiculus bears three major types of sensilla: the conspicuous, sharp-tipped trichoid sensilla, the translucent, club-shaped basiconic sensilla, and the tiny, coeloconic sensilla with prominent sockets (Fig. 1) (Link, 1983;Mindek, 1968;Riesgo-Escovar et al, 1997b;Venkatesh and Singh, 1984). Electrophysiological recordings have assigned an olfactory function to all of them (Clyne et al, 1997;de Bruyne et al, 2001;Siddiqi, , 1991see below).…”
Section: Introductionmentioning
confidence: 97%
“…Some mutants show morphological deficiencies, such as those on the lozenge gene implicated in the development of the antennae and palps. These mutants show a complete absence of basiconic sensilla on the antenna (Riesgo-Escovar et al, 1997a), along with a reduction in size and absence of pores on the basiconic sensilla on the palps (Riesgo-Escovar et al, 1997b). Electrophysiological responses from the palps and antennae, as well as behavioural responses to olfactory stimulants in lozenge mutants are strongly reduced compared to wild-type flies (Venard and Stocker, 1991;Riesgo-Escovar et al, 1997a,b).…”
Section: Introductionmentioning
confidence: 99%